THE PARADOX OF A YOUNG NATION: THE ECONOMICS OF PREMATURE AGEING IN A DEMOGRAPHICALLY YOUNG INDIA - Singh, Henam Pearlemerson (International Journal of Research -GRANTHAALAYAH, 2025)
India is widely regarded as a young nation with significant demographic potential. Yet beneath this aggregate youthfulness lies a growing phenomenon of premature ageing, marked by early onset of chronic disease, functional decline, and economic vulnerability during working ages. This paper examines the economic foundations of premature ageing in India by linking epidemiological transition, informal labour, environmental stress and social inequality to productivity loss and household insecurity. It argues that it threatens India’s demographic dividend and calls for a life course policy response integrating prevention, healthcare, labour adaptation and social protection.